Feedlot diets with soybean oil, selenium and vitamin E alters rumen metabolism and fatty acids content in steers - Paiva Ferreira, Adriano Vinicius de; Cominotte, Alexandre [UNESP]; Ladeira, Marcio M.; Casagrande, Daniel R.; Teixeira, Priscilla D.; van Cleef, Eric; Ezequiel, Jane [UNESP]; Castagnino, Pablo [UNESP]; Machado Neto, Otavio R. [UNESP] (Elsevier B.V., 2020)
The objective of this experiment was to evaluate the effect of combining selenium (Se) and vitamin E (E) on intake, total digestibility and omasum escape of fatty acids in steers fed diets supplemented with high concentration of soybean oil (SO). Five rumen cannulated Tabapud steers (BW = 398 +/- 28.7 kg) were used in a 5 x 5 Latin square design with a 2 x 2 + 1 factorial arrangement Soybean oil diets without Se (Se-) or with Se at 5 g animal per day (Se + ) combined with SO diets without vitamin E (E-) or with vitamin E at 1500 IU animal per day (E + ) and an added treatment without additional oil (WAO). Diets were formulated to contain 124 g/kg of crude protein (CP) in the dry matter (DM) and included corn silage, ground corn, soybean meal, soybean oil, corn gluten meal and mineral supplement. Soybean oil was added to diets at 60 g/kg of dietary DM. Each experimental period lasted 21 days with 14 days of adaptation to the diets, and 7 days for data collection. There were no effects of combining selenium or vitamin Eon DM and nutrients intake (P > 0.10). The DM intake decreased in diets with supplemental SO compared to WAO diets (P = 0.02). Soybean oil supplementation decreased the total digestibility of DM (P = 0.05), OM (P = 0.05), NFC (P = 0.04) and aNDFom (P < 0.01). However, the total EE digestibility increased (P < 0.01). Diets did not affect the efficiency of microbial protein synthesis (P >= 0.10). At the same time, SO diets decreased the excretion of microbial N and the total protozoal counts (P <= 0.05). There was no interaction for treatment x time on pH, VFA and NH3-N (P >= 0.10). The individual VFA, mol/100 mol concentration was similar among treatments (P >= 0.10; Table 5). The total VFA content, mM increased 6.5 % in Se diets compared to no Se supplementation (P = 0.068). There was a reduction in the rumen NH3-N content in SO diets compared to WAO (P < 0.05). Soybean oil diets increased the concentration of polyunsaturated fatty acids (PUFA) and linoleic acid (C18:2 trans-10 cis-12; P < 0.01) in the omasum and it tended to enhance with selenium supplementation (P = 0.07). The combination of selenium and vitamin E in feedlot diets with high soybean oil inclusion, contrary to our hypothesis, do not improve rumen fermentation and nutrient utilization. Future studies should use lower inclusions of soybean oil in beef cattle diets to avoid possible suppression of supranutritional effects of selenium and vitamin E on ruminal metabolism and biohydrogenation.
Keywords: Fermentation; Protozoa; Selenium; Soybean oil; Vitamin E